Missing ethics: A proposal for responsible conduct of research training in political science in interdisciplinary comparison. - Chekenya, Nixon S (International Political Science Review, 2026)
Science depends on trust, integrity and accountability. Yet compared to related disciplines, political science has been slow to institutionalize responsible conduct of research (RCR) education. This paper addresses that gap by presenting an empirical audit of RCR training across the top 50 political science graduate programmes in the United States. The findings reveal that while methods and quantitative training are near-universal, formal ethics instruction is rare or entirely absent in most programmes. Drawing on lessons from economics, psychology and biomedical sciences, I show how the lack of structured RCR education threatens the credibility, reproducibility and ethical integrity of political science research. I then propose a modular, credit-bearing RCR course tailored to the methodological and normative challenges faced by political scientists, including fieldwork, experimental design, authorship norms and data transparency. By embedding RCR into graduate curricula, political science can better prepare future scholars to navigate ethical dilemmas, prevent misconduct, and align with evolving expectations from funders and journals. This article extends the recent work of Chekenya and Misra by focusing specifically on graduate education in political science, and offers practical guidance for departments, professional associations and educators committed to cultivating a culture of ethical research. JEL Classification: A11, B41, Q10